Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan dengan Pengungkapan Corporate Social Responsibility Sebagai Variabel Moderasi: Studi pada Perusahaan Healthcare yang Terdaftar di BEI Periode 2019-2024 - Anasyifa Rachelita; Intan Puspitasari; Agus Saur Utomo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The healthcare industry is a dynamic and rapidly growing sector in indonesia. Between 2019 and 2024, the healthcare industry experienced positive growth in profits and assets, but stock prices declined during the same period. This study was conducted to examine the effect of financial performance on company value, with corporate social responsibility disclosure as s moderating variable in healthcare companies. The sample used in this study consists of five companies: PT Industri Jamu dan Healthcare Sido Muncul Tbk, PT Kalbe Farma Tbk, PT Indofarma Persero, PT  Siloam International Hospital Tbk, and PT Merck Tbk. The research data consists of panel data obtained from annual financial reports and Corporate Social Responsibility disclosure reports. Data analysis was conducted using Moderated Regression Analysis with Eviews software. The results of this study indicate that: (1) the current ratio has a positive but insignificant effect on company value; (2) return on assets has a positive and significant effect on company value; (3) corporate social responsibility on company value.